Development of an MCL-1-related prognostic signature and inhibitors screening for glioblastoma - Zhang, Ao; Guo, Zhen; Ren, Jia-xin; Chen, Hongyu; Yang, Wenzhuo; Zhou, Yang; Pan, Lin; Chen, Zhuopeng; Ren, Fei; Chen, Youqi; Zhang, Menghan; Peng, Fei; et al. (Frontiers in Pharmacology, 2023)
The effect of the conventional treatment methods of glioblastoma (GBM) is poor and the prognosis of patients is poor. The expression of MCL-1 in GBM is significantly increased, which shows a high application value in targeted therapy. In this study, we predicted the prognosis of glioblastoma patients, and therefore constructed MCL-1 related prognostic signature (MPS). The RNA-seq and clinical data of GBM samples were obtained from TCGA (Cancer Genome Atlas database) website. The enrichment level of immune cells and the expression level of immune checkpoint genes were analyzed. The 449 differentially expressed genes were next analyzed, and MCL-1-associated prognostic signature were constructed by Least Absolute Shrinkage and Selection Operator (LASSO) cox regression analysis. Univariate and multivariate cox analysis showed that 5 genes could be used as independent factors to predict the prognosis of glioblastoma patients. Based on the above analysis, a new nomogram was constructed to predict the survival of glioblastoma patients. In addition, using a series of computer-aided techniques, two more plausible lead compounds, ZINC000013374322 and ZINC000001090002, were virtually selected. With potential inhibitory effects on MCL-1, these compounds provide a basis for the design and further development of MCL-1 specific small molecule inhibitors. In summary, this study analyzed the effect of MCL-1 on the prognosis of glioblastoma patients from the perspective of immunology, constructed a new prognostic model to evaluate the survival rate of patients, and further screened 2 MCL-1 small molecule inhibitors, which provides new ideas for the treatment and prognosis of glioblastoma.